Pengaruh Asap Obat Nyamuk Bakar Terhadap Lama Hidup, Kernampu.an Bertelur, Daya Tetas Telur dan Daya Tetas Larva Aedes aegypti - Supargiyono, Supargiyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Mosquito incense coil had been widely use among the households of Indonesian community as an effort to prevent mosquito bites. Nevertheless, its definite influence to the mosquitos biology is still not yet known.This study was conducted to ensure the influence of mosquito incense coil smoke to the longevity, egg production capability, egg hetching capacity and instar emerging capacity of Aedes aegypli mosquito in Yogyakarta.Aedes aegypli mosquitos were collected either from urban or rural area, reared in the laboratory and prepared for laboratory testing. Incense burning was done in a closed-testing room, in six different periods from 5 minutes to 180 minutes. Some biological aspects such as longevity, egg production, egg hetching and instar emerging were observed.It can be concluded that mosquitos incense smoke has either chase out effect or killing effect to Ae. aegypti mosquitos. It is also clear that with the incense burner period of 30 minutes will prolong the longevity, reduce egg production capability, reduce egg hetching capacity and reduce instar emerging capacity. On the incense burning period of 120 minutes, 81.7% of Ae. aegypti tested were killed, and furthermore, in the incense burning period of 180 minutes, all Ae. aegypti tested were killed.Key Words: egg production capability -- egg hetching capacity Ã¢â¬â instar emerging capacity chase out effect Ã¢â¬â mosquito incence coil